A self-adaptive evolutionary algorithm for a fuzzy multi-objective hub location problem: An integration of responsiveness and social responsibility. (June 2017) - Zhalechian, Mohammad; Tavakkoli-Moghaddam, Reza; Rahimi, Yaser
Abstract: In this paper, we present a new multi-objective model for a hub location problem under uncertainty. This model simultaneously considers economic, responsiveness and social aspects in designing a hub-and-spoke network. An M / M / c queuing system is used to calculate waiting time at each hub node and maximize responsiveness. Employment and regional development are selected as social responsibility measures in the proposed model. Furthermore, a hybrid two-phase solution method is proposed based on possibilistic programming, fuzzy multi-objective programming and an efficient algorithm, called self-adaptive differential evolution algorithm. Finally, several numerical experiments and sensitivity analyses are carried out to assess the proposed model and the solution method.